2009
DOI: 10.1007/s10439-008-9630-9
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Effect of False Vocal Folds on Glottal Flow and Vocal Fold Vibration During Phonation

Abstract: The false vocal folds are believed to be components of the acoustic filter that is responsible for shaping the voice. However, the effects of false vocal folds on the vocal fold vibration and the glottal aerodynamic during phonation remain unclear. This effect has implications for computational modeling of phonation as well as for understanding laryngeal pathologies such as glottal incompetence resulting from unilateral vocal fold paralysis. In this study, a high fidelity, two-dimensional computational model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 39 publications
6
97
2
4
Order By: Relevance
“…Interestingly we have found that flow develops a preferential direction of deflection (left in this case) which can persist for many cycles. Note that in 2D simulations (Zheng et al, 2009) the jet deflection switched directions very rapidly from cycle-to-cycle but the switching was less frequent in the 3D planar model (Zheng et al, 2011b). The current model, which has additional 3D features than the previous 3D planar model, shows an even longer timescale associated with direction switching in the glottal jet, which seems to be consistent with the effect of threedimensionality.…”
Section: B Glottal Jet Evolutionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly we have found that flow develops a preferential direction of deflection (left in this case) which can persist for many cycles. Note that in 2D simulations (Zheng et al, 2009) the jet deflection switched directions very rapidly from cycle-to-cycle but the switching was less frequent in the 3D planar model (Zheng et al, 2011b). The current model, which has additional 3D features than the previous 3D planar model, shows an even longer timescale associated with direction switching in the glottal jet, which seems to be consistent with the effect of threedimensionality.…”
Section: B Glottal Jet Evolutionmentioning
confidence: 92%
“…Initial attempts were mostly with two-dimensional (2D) models (Zhao et al, 2001;Zhao et al, 2002;Zhang et al, 2002;Alipour and Scherer 2004). Furthermore, immersed boundary method based solvers have also found an increased use in these models (Duncan et al, 2006;Luo et al, 2008;Luo et al, 2009;Zheng et al, 2009) due to their inherent ease of application to complex biological problems with moving/deforming boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have shown that the largescale asymmetric glottal jet deflection (AGJD) in the mediallateral direction does occur during phonation both inside the glottis Plesniak, 2006a,b, 2010) as well as in the supraglottal region (Neubauer et al, 2007;Dreschsel and Thomson, 2008;Zheng et al, 2009). Furthermore, in many studies, the glottal jet has been found to exhibit stochastic cycle-to-cycle variations in its trajectory Plesniak, 2006a,b, 2010;Neubauer et al, 2007;Dreschsel and Thomson, 2008;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in many studies, the glottal jet has been found to exhibit stochastic cycle-to-cycle variations in its trajectory Plesniak, 2006a,b, 2010;Neubauer et al, 2007;Dreschsel and Thomson, 2008;Zheng et al, 2009). There is also evidence that asymmetry in the glottal flow can have an impact on pressure losses, vocal-fold vibration, and sound production (Triep et al, 2005;Dreschsel and Thomson, 2008;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These include studies with fixed vocal folds (e.g. [12,13,14,15]), forced vocal fold oscillation [16,17,6,18,19,20,21,22,23] and models with the airflow fully coupled to elastic tissue oscillations [24,25,26,27,28,29,30]. Only a few of these computational studies [24,12,14,15,22] solve the flow field in 3D, and most of them on a static geometry.…”
Section: Previous Work In the Fieldmentioning
confidence: 99%